2009
DOI: 10.1523/jneurosci.4742-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Cav1.3 Channel Voltage Dependence, Not Ca2+Selectivity, Drives Pacemaker Activity and Amplifies Bursts in Nigral Dopamine Neurons

Abstract: Ca v 1.3 (␣1D) L-type Ca2ϩ channels have been implicated in substantia nigra (SN) dopamine (DA) neuron pacemaking and vulnerability to Parkinson's disease. These effects may arise from the depolarizing current and cytoplasmic Ca 2ϩ elevation produced by Ca v 1.3 channels at subthreshold membrane potentials. However, the assumption that the Ca 2ϩ selectivity of Ca v 1.3 channels is essential has not been tested. In this study the properties of SN DA neuron L-type Ca 2ϩ channels responsible for driving pacemaker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
133
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(151 citation statements)
references
References 30 publications
17
133
1
Order By: Relevance
“…The subthreshold Ca 2+ -K + oscillatory mechanism underlies the generation of low frequency background firing in a significant subpopulation of DA neurons [7][8][9][10][11][12][13][14][15][16][17][18]51]. However, a number of studies suggest a contribution of Ca 2+ -independent currents to oscillations [26,19,25,27,46]. In accord with these studies, we found that, if considered in isolation, the Ca 2+ -K + oscillatory mechanism provides type II excitability, which is incompatible with the experiments reproduced above.…”
Section: Influence Of Intrinsic Currents On the Type Of Excitabilitysupporting
confidence: 73%
“…The subthreshold Ca 2+ -K + oscillatory mechanism underlies the generation of low frequency background firing in a significant subpopulation of DA neurons [7][8][9][10][11][12][13][14][15][16][17][18]51]. However, a number of studies suggest a contribution of Ca 2+ -independent currents to oscillations [26,19,25,27,46]. In accord with these studies, we found that, if considered in isolation, the Ca 2+ -K + oscillatory mechanism provides type II excitability, which is incompatible with the experiments reproduced above.…”
Section: Influence Of Intrinsic Currents On the Type Of Excitabilitysupporting
confidence: 73%
“…First, we observed extremely high expression levels of the big potassium (BK) channel (encoded by the potassium large conductance calcium-activated channel gene; Kcnma1) and the Cacnb3 (voltage-gated calcium channel auxiliary b3 subunit). In addition, the L-type voltage-gated calcium channel a1d (Cacna1d, also known as Cav1.3), although not present in the microarray, is highly expressed in these neurons (see Allen Brain Atlas: http://mouse.brain-map.org/experiment/show/68798037) and has been shown to drive pacemaker activity in dopamine (DA) neurons (22). We were also interested in the pacemaking HCN channels, which are differentially expressed in the habenula (16,23).…”
Section: Trap Analysis Of Cholinergic Mhb Neurons Reveals Enrichment Ofmentioning
confidence: 99%
“…Our contention that Cav1.3 channels are not necessary for pacemaking has been challenged in a recent article (97). The crux of their argument is that they can experimentally restart pacemaking that has been halted with high concentrations of DHP by using dynamic current clamp to reintroduce Cav1.3 channels into the soma.…”
Section: Surmeier Et Almentioning
confidence: 99%